Solitary Neurofibroma Mimicking Giant Cell Tumor of The Upper Cervical Spine: A Case Report - Ermawan, Rieva; Renata, Felicia; Muzakkiyafi, Mohammad; Corrigan, Hubertus (Universitas Airlangga, 2025)
Background: Spinal neurofibromas are benign peripheral nerve sheath tumors typically occurring in the thoracic region. Involvement of the C2 vertebra is particularly rare. Atypical presentations of solitary neurofibromas can pose diagnostic challenges when their radiological features resemble other neoplastic entities. Case Report: A 35-year-old male presented with a 3-month history of neck pain and no history of trauma. Physical examination revealed mild bulging and localized tenderness in the posterior neck, with restricted neck extension to 30 degrees. Plain radiography showed a round, expansile lytic lesion with well-defined, nonsclerotic borders on the C2 spinous process, while MRI confirmed enhancing solid components and extensive bone involvement, indicative of a giant cell tumor. The histopathology from the core needle biopsy was inconclusive, showing few inflammatory cells and no evidence of malignancy. The lesion was marginally resected from a posterior approach, achieving only subtotal resection to preserve the vertebral artery. Histopathological analysis from the open biopsy confirmed the diagnosis of neurofibroma. At the 3-month follow-up, postoperative imaging showed the residual tumor. Despite this, the patient reported significant neck pain relief.Discussion: Radiography is insufficient for differentiating spinal tumors; therefore, histopathological biopsy is necessary for an accurate diagnosis. Open biopsy offers higher diagnostic accuracy than core needle biopsy.Conclusion: Neurofibroma should be considered in differential diagnosis for patients initially suspected of giant cell tumors based on radiological findings.